Organic contaminants' bio-degradation with Fe (Ⅲ) - TAN Ying-ying; ZHENG Ping; JIANG Xin (浙江大学学报. 农业与生命科学版)
Some ferric reducing microorganisms can oxidize some contaminants to carbon dioxide using Fe (Ⅲ) as sole electron acceptor. With these microorganisms, biological-remedial technology can be developed to deal with the polluted environment in situ. In this article, the ferric microorganisms, dissimilatory Fe (Ⅲ) reduction, contaminants' degradation with Fe (Ⅲ) reducing and its potential use in bioremedy were reviewed.